2014
DOI: 10.1177/0960327114532385
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin induces hormonal imbalance and oxidative damage in the erythrocytes and uterus but not in the ovary of rats

Abstract: Artemisinin is an antimalarial drug previously reported to induce neurotoxicity and embryotoxicity in animal models. This study investigated the erythrocytes and reproductive toxicity potentials of artemisinin in female rats. Animals were randomly divided into four study groups of eight rats each. The control group (group I) received corn oil, the vehicle, while groups II–IV were orally exposed to 7, 35 and 70 mg kg−1 day−1 of artemisinin, respectively, by gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…Differences in the oxidative status between the uterus and the ovaries also have been reported by Farombi et al [41]. Using an antimalarial drug (artemisinin), they showed that it caused oxidative damage of lipids in the uterus, manifested by an increase in the concentration of MDA.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Differences in the oxidative status between the uterus and the ovaries also have been reported by Farombi et al [41]. Using an antimalarial drug (artemisinin), they showed that it caused oxidative damage of lipids in the uterus, manifested by an increase in the concentration of MDA.…”
Section: Discussionsupporting
confidence: 52%
“…Ovaries seem to be protected primarily against the formation of free radicals. In the study by Farombi et al [41] the concentration of H 2 O 2 , as a marker of the intensity of free radicals reactions, did not change in the ovaries, but increased significantly in the uterus.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, MDA levels increased significantly in the kidney of diabetic rats when compared to the normal control ( Table 4 ). The increase in MDA level in diabetic groups suggests damage to cell membrane lipids in a diabetic state, which could lead to increased generation of ROS [ 66 ]. Subsequent treatment with MO led to a significant ( p < 0.05) decrease in MDA levels in diabetic rats reducing lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of ART to suppress cell proliferation and hormonal secretion in different cell types including GH 3 cells [3,4,29,30]. It is important to determine to what extent ART-induced neurological or ototoxic actions is linked to its…”
Section: Discussionmentioning
confidence: 99%